ANALISIS PESAN IKLAN KAMPANYE DIGITAL CAPRES-CAWAPRES PADA PEMILIHAN PRESIDEN 2024 - Natanael Aditanto; Dewi Kartika Sari (JIKE: Jurnal Ilmu Komunikasi Efek, 2025)
The presidential election is the main agenda in the democratic system in Indonesia. In the 2024 general election, presidential and vice presidential candidates use various campaign strategies to influence voters, one of which is a digital campaign by utilizing existing digital media. Digital campaign advertising, including promotions on social media, websites, and other online platforms, plays an important role in conveying candidates' messages, visions, and programs. The use of social media is one of the strategies to convey the content of advertising messages in digital campaigns in reaching, reaching and influencing the wider community. The method used in this research is a qualitative method with the use of theory. The type of research approach used is Ferdinand de Saussure's semiotic analysis approach using signifier and signified as a reference. This research takes two data sources, namely primary data in the form of digital campaign advertisements carried out by 2024 presidential and vice presidential candidates through social media and secondary data sources obtained from journals, books and other literature sources that support the analysis of primary data. This research focuses on analyzing the meaning contained in the lyrics (captions) of presidential-vice presidential campaign advertisements on YouTube video sharing. The results of this study indicate the existence of meanings that contain signifier and signified in the lyrics (captions) of presidential and vice presidential campaign advertisements in YouTube video sharing. Each pair of presidential and vice presidential candidates puts a different emphasis on their advertising messages.